Food security, agricultural investment, and climate change: A global empirical analysis - Almughni, Muhammad Afdha Alif; Kusumawardani, Deni; Rohman, Muhammad Syaikh (Journal of Food Technology Research, 2025)
The conditions of world hunger are centered on countries on the African continent and a small part of the Asian continent. This condition highlights the inequality of hunger conditions globally. The situation is exacerbated by rising food prices and the conflict between Ukraine and Russia, which has caused an increase in agricultural input prices. To address these challenges, agricultural investment is necessary. However, another factor threatening food security is climate change. Therefore, this study aims to analyze the influence of agricultural investment and climate change on food security, as proxied by food availability globally and based on continental groupings: Africa, Asia, Europe, Oceania, North America, and South America. This study uses data from 159 countries over the period 2002-2022, sourced from the World Bank and FAOSTAT, and processed using the panel regression method. Empirical results show that agricultural investment has a positive effect on food security. Climate change, with temperature indicators, has a negative effect on food security globally and on the Africa, Europe, and Oceania continents, but does not affect Asia, North America, and South America. Climate change, with rain indicators, has a negative effect on food security globally and on Africa, Asia, Europe, North America, and South America, but does not affect Oceania.